Actualidade Económica de Moçambique: Transitando para um crescimento mais inclusivo (World Bank Group, 2018)
Buoyed by a drop in inflation and the advancement of one of two major gas projects, the Mozambique Economic Update (MEU): Shifting to Inclusive Growth notes that the country is more stable since the 2016 debt crisis triggered the economic slump, but growth prospects are limited. Gross domestic product (GDP) growth was an average 3.8% in 2016 and 2017 and is expected to reach a slightly lower rate of 3.3% in 2018. Services such as tourism, transport and finance—all hardest hit by the crisis—have shown a modest increase in growth, the report says, however these gains were offset by slowed growth in the extractives sector. Mozambique’s growth opportunities also hinge on the recovery of consumer spending, especially in services, which had been the largest driver of growth before 2016, the report notes. A strong policy focused on reducing macroeconomic uncertainty and enhancing investment would help lay the foundation for complete recovery and more inclusive growth, the report says.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; development partners / parceiros de cooperação; inclusive growth / crescimento inclusivo

Mozambique Economic Update: Shifting to More Inclusive Growth (World Bank Group, 2018)
Buoyed by a drop in inflation and the advancement of one of two major gas projects, the Mozambique Economic Update (MEU): Shifting to Inclusive Growth notes that the country is more stable since the 2016 debt crisis triggered the economic slump, but growth prospects are limited. Gross domestic product (GDP) growth was an average 3.8% in 2016 and 2017 and is expected to reach a slightly lower rate of 3.3% in 2018. Services such as tourism, transport and finance—all hardest hit by the crisis—have shown a modest increase in growth, the report says, however these gains were offset by slowed growth in the extractives sector. Mozambique’s growth opportunities also hinge on the recovery of consumer spending, especially in services, which had been the largest driver of growth before 2016, the report notes. A strong policy focused on reducing macroeconomic uncertainty and enhancing investment would help lay the foundation for complete recovery and more inclusive growth, the report says.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; development partners / parceiros de cooperação; inclusive growth / crescimento inclusivo

GFF Guidance Note: Inclusive Multi-stakeholder Country Platforms in Support of Every Woman Every Child - Global Financing Facility (Global Financing Facility, 2018)
The aims of this paper are: 1) to highlight how multi-stakeholder country platforms, built on development effectiveness principles, in line with the globally agreed recommendations of IHP+2, can be reinforced within the framework of the Global Strategy and its supporting mechanisms and are key to the Global Strategy’s successful implementation; and 2) to lay out key considerations for new multi-stakeholder country platforms, along with the relevant mechanisms and a minimum set of standards to support the process of national coordination among actors engaged in RMNCAH. This guidance note is intended to serve as a resource for countries committed to implementing the Global Strategy. This includes the 62 high-burden, low- and lower-middle income countries that are eligible to receive resources from the GFF Trust Fund. It will build on lessons from countries that have already developed or are currently developing prioritized RMNCAH Strategies or Investment Cases (IC)4 aligned with their broader national health plans and planning cycles and processes, for purposes of mobilizing resources, including from the GFF Trust Fund and other sources of funding. The GFF, H6 and PMNCH seek to bring together a broad set of partners and leverage their unique roles, comparative advantages and value added to maximize impact for improved outcomes for women, children and adolescents.
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Rest of the World / Resto do Mundo; GFF (Global Financing Facility); Health PEA; L - english / inglês; civil society / sociedade civil; development partners / parceiros de cooperação; gender / género; health / saúde; youth / juventude

Mozambique Country Strategy Paper 2018 -2022. Supporting Mozambique towards the HIGH5s - Santos, Almeida (African Development Bank, 2018)
The African Development Bank Group’s Country Strategy Paper (CSP) 2018-22 for Mozambique comes at a time when the country adopted its long term development strategy ‘ENDE’ 2015-35. The CSP was prepared on the basis of extensive consultations held with the Government of Mozambique, Development Partners, the private sector and the civil society. The main objective of the ENDE is the improvement of the livelihoods of the population through the structural transformation of the economy, and the expansion and diversification of national production. The strategy is to be implemented through the 5-Year Government Programs (PQGs). The PQG goal for 2015-19 is to increase employment, productivity and competitiveness to improve living conditions of Mozambicans, in an environment of peace, harmony and tranquillity, while consolidating democracy and inclusive participatory governance.
Keywords: G - Mozambique / Moçambique; L - english / inglês; Northern PEA; development partners / parceiros de cooperação

The Project for Supporting the Promotion of Nacala Corridor Development - Final Report - Japan International Cooperation Agency (JICA) (Japan International Cooperation Agency (JICA), 2018)
Final JICA report on Nacala Corridor Development Project, whose objectives include: to clarify organizations for promoting and coordinating the implementation of development strategies for the Nacala Corridor Region in accordance with PEDEC-Nacala and to prepare for the implementation of high priority projects in accordance with PEDEC-Nacala. The study project commenced in April 2012 and the final study report was produced in April 2015.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - Nacala; G - central / centro; G - north / norte; GD - Lichinga; GP - Cabo Delgado; GP - Nampula; GP - Niassa; GP - Tete; GP - Zambézia; L - english / inglês; development partners / parceiros de cooperação; extractive industries / indústrias extractivas; infrastructure / infrastrutura; natural resources / recursos naturais; private sector / setor privado

GFF Civil Society Engagement Strategy Addendum - Adolescent and Youth (AY) - Global Financing Facility (Global Financing Facility, 2018)
The Global Strategy for Women’s, Children’s and Adolescents’ Health 2016-30 highlights the importance of adolescent health and well-being as being essential to achieving the Sustainable Development Goals (SDG) by 2030. For adolescents to survive, thrive and transform their societies, the global community needs to invest in their health and well-being. Today’s adolescents are well-positioned to mobilize their peers, advocate for increased resources for sexual and reproductive health and rights, influence their governments to invest in addressing their needs, and demand accountability for commitments related to their health and development. The Global Financing Facility (GFF) Civil Society Engagement Strategy (CSES) and related implementation plan provide a clear framework for civil society organizations’ (CSOs) contribution to the improvement of health outcomes through coalition strengthening, meaningful participation in multi-stakeholder country platforms responsible for coordinating health plans and their implementation,1 and coordinated action in support of the achievement of national sexual, reproductive, maternal, newborn, child and adolescent health (SRMNCAH) goals. Youth and adolescent led organizations should use the CSES as the basis for their engagement in the GFF processes both at the global and national levels. This Adolescent and Youth (AY) addendum to the CSES outlines a deliberate approach to ensuring youth representation in the processes led by the GFF Civil Society Coordinating Group2 (CSCG) to ensure their meaningful and active participation in the design, implementation, monitoring and evaluation of their country investment case.
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Rest of the World / Resto do Mundo; GFF (Global Financing Facility); Health PEA; L - english / inglês; development partners / parceiros de cooperação; health / saúde; youth / juventude

Moçambique Avaliação de Pobreza: Crescimento Forte, Mas Não Partilhado (World Bank Group, 2018)
Mozambique has experienced strong and sustained economic growth in the last two decades. Growth of its Gross Domestic Product (GDP) expanded at an annual average rate of 7.2 percent between 2000 and 2016, making it one of the fastest-growing countries in Sub-Saharan Africa (SSA). The economic expansion has boosted incomes and living standards. GDP per capita, for instance, grew annually on average by 4 percent over the same period, climbing from 561 US dollars to 1,128 US dollars (2011 PPP). Growth has been supported by a rebounding agricultural sector, particularly in the first phase of the post-war period, increased productivity in trade, transport and communications and financial services, sound macroeconomic management, large-scale foreign investments projects and significant donor support. More recently, however, growth has slowed down due mainly to macroeconomic factors and severe natural disasters.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; development partners / parceiros de cooperação; poverty / pobreza

Mozambique Poverty Assessment: Strong But Not Broadly Shared Growth (World Bank Group, 2018)
Mozambique has experienced strong and sustained economic growth in the last two decades. Growth of its Gross Domestic Product (GDP) expanded at an annual average rate of 7.2 percent between 2000 and 2016, making it one of the fastest-growing countries in Sub-Saharan Africa (SSA). The economic expansion has boosted incomes and living standards. GDP per capita, for instance, grew annually on average by 4 percent over the same period, climbing from 561 US dollars to 1,128 US dollars (2011 PPP). Growth has been supported by a rebounding agricultural sector, particularly in the first phase of the post-war period, increased productivity in trade, transport and communications and financial services, sound macroeconomic management, large-scale foreign investments projects and significant donor support. More recently, however, growth has slowed down due mainly to macroeconomic factors and severe natural disasters.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; development partners / parceiros de cooperação; poverty / pobreza

Country Results Brief 2018 - Mozambique - African Development Bank (African Development Bank, 2018)
Over the last decade, Mozambique has been one of the fastest-growing African economies, enjoying average economic growth of about 8% between 2004 and 2015. It received strong support from the international community during the period (for example, in 2014 it received US$2 billion in official development assistance). In parallel, the country has embarked on major reforms — especially fiscal reforms and tax administration — and has opened up to foreign investment, particularly for the exploitation of its natural resources.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; agriculture / agricultura; development partners / parceiros de cooperação; governance / governação; infrastructure - energy / infrastrutura - energia; infrastructure - roads / infrastructura - estradas; infrastructure / infrastrutura; private sector / setor privado